PROBLEMATIKA GURU AL-QUR’AN HADITS DALAM MENGATASI KESULITAN MEMBACA AL-QUR’AN DAN IMPLIKASINYA TERHADAP PEMBELAJARAN EKONOMI DI MTS AL MUNAWWARAH KOTA JAMBI - Hilda Salsabila; Muhammad Fadhil (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2026)
This study aims to analyze the problems faced by Al-Qur’an Hadith teachers in overcoming students’ difficulties in reading the Qur’an among seventh-grade students at MTs Al Munawwarah, Jambi City, and their impact on the effectiveness of Economics learning. Using a descriptive qualitative method, data were collected through observation, in-depth interviews, and documentation. The results indicate that the main problems include the heterogeneity of students’ educational backgrounds, limited teaching staff, insufficient time allocation, and low students’ learning motivation. These conditions significantly affect Economics learning, where students experience cognitive barriers in understanding Islamic Economics materials based on naqli sources. The inability to read the Qur’an leads to ineffective internalization of muamalah values and hinders the achievement of the Economics curriculum. The efforts made by teachers include class grouping based on students’ abilities (differentiation), the implementation of additional tahsin/tahfidz programs, and intensive guidance outside school hours. This study concludes that strengthening Qur’anic literacy is an essential prerequisite for improving students’ enthusiasm and understanding in Economics subjects integrated with Islamic values